DIGITAL MARKETING STRATEGY FOR MILLENNIALS AND GEN Z: A LITERATURE REVIEW - Al-Amin; Kurnia Budhy Scorita (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to identify and analyse effective digital marketing strategies for millennials and Gen Z through a literature review. Both generations show characteristics of consumption behaviour that are highly influenced by the development of digital technology, with a high tendency towards visual, interactive, and authentic content on various social media platforms. The results of the study show that marketing strategies that promote personalisation, collaboration with influencers, and involvement in social and sustainability issues are better able to attract the attention and build loyalty of young consumers. In addition, the use of technology such as artificial intelligence, short videos, and mobile-first optimisation is a determining factor in the success of digital campaigns. By understanding the differences and similarities between the characteristics of millennials and Gen Z, companies can design digital marketing strategies that are relevant, innovative, and impactful in increasing engagement and sales in the digital era.